Two-dimensional and three-dimensional distinct element numerical stability analyses for assessment of the west wall cutback design at Ok Tedi Mine, Papua New Guinea - de Bruyn, I.A.; Coulthard, M.A.; Baczynski, N.R.P.; Mylvaganam, J. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Detailed evaluations for finalisation of the design for the west wall cutback at the Ok Tedi copper-gold mine in Papua New Guinea have been ongoing since 2010. The geotechnical rock mass characterisation, structural model and conceptual hydrogeological model have been progressively updated since 1997, and have been significantly advanced during recent feasibility studies. The pit is being progressively deepened with ongoing mining, and a cutback of the west wall is being planned that would result in a final wall height of 1,000 m. The wall will be cutback by up to 300 m over a crest length of greater than 1,500 m, which will take place over a period of approximately 13 years. A comprehensive set of 2D distinct element analyses were completed in 2011 for assessment of the stability of the west wall final design. Depressurisation of the cutback slope was indicated to be of great importance, and measures for depressurisation were taken into account in the supporting analyses. Additional field investigations and assessments for confirmation of the design performance were carried out in 2012 and are ongoing in 2013. The key aspect of this work involved further distinct element analyses for assessment of the slope performance in three dimensions, particularly in the context of the effects of major structures, joint sets, pit wall curvature and pore water pressures as the slope cutback is developed. The extreme size and complexity of the 3D model necessitated simplifications to the geotechnical domains and structural inputs in order to create a practical working model. As expected, the 3D analyses provided Factors of Safety for slope instability significantly greater than those obtained from the original 2D analyses. However, it is most important to understand the context and limitations of these results when making final decisions on design outcomes. For this reason, selected additional 2D analyses were carried out in order to assess the sensitivity of the results to simplifications in the geotechnical domains and structural inputs and to the coarser block size necessary for the very large 3D model.